Caffeine Consumption and General Health in Secondary School Children: A Cross-sectional and Longitudinal Analysis - Richards, Gareth; Smith, Andrew P. (Frontiers in Nutrition, 2016)
Although caffeine is sometimes associated with beneficial effects in adults, the substance may be dangerous if intake is too high. This concern is particularly relevant in regards to children and adolescents, as consumption of energy drinks may be particularly high in such populations. For this reason, the current study examined data from the Cornish Academies Project to determine whether caffeine intake in secondary school children was related to responses to a single-item measure of general health. Two cross-sections of data were available: questionnaires were completed by 2030 at baseline, by 2307 at 6-month follow-up, and by 1660 at both time-points. Relationships were, therefore, explored both cross-sectionally and longitudinally. High caffeine consumption (i.e., 1000 mg/week) was associated with low general health in both cross-sections of data, and analyses of individual caffeine sources suggested that the effects related specifically to cola and energy drinks. However, after controlling for additional aspects of diet, demography, and lifestyle, total weekly intake only remained significantly associated with general health at the latter time-point. Further to this, null findings from cross-lag and change-score analyses suggest that caffeine and general health were unlikely to be causally linked in this sample. However, due to methodological limitations, such as the two cross-sections of data being collected only 6 months apart, it is suggested that further longitudinal and intervention studies are required in order for firm conclusions to be drawn.